Percutaneous treatment of a superior mesenteric artery pseudoaneurysm and arteriovenous fistula with coil embolization: a case report - Alparslan Kılıç; Mikail Yarlıoğlueş; Elif Ergün; Yılmaz Ünal; Sani Namık Murat (KARE Publishing, 2017)
Visceral artery pseudoaneurysm and arteriovenous fistula following penetrating abdominal injuries is a rarely observed complication. Presently described is the case of a 44-year-old male admitted to the hospital after having previously experienced penetrating abdominal trauma. The patient had developed a pseudoaneurysm in the superior mesenteric artery and an arteriovenous fistula between the superior mesenteric artery and vein following surgery. The patient underwent successful coil embolization procedure and he was discharged 1 day after intervention.